Value of growth arrest lines for predicting treatment effect on children with distal tibial epiphysis fractures - Wang, Sisheng; Zheng, Shaoluan; Liu, Qi; Wang, Chengyun; Liu, Maosheng; Su, Lianbin (Frontiers in Pediatrics, 2023)
Objective This study aims to explore whether growth arrest lines can predict epiphyseal fracture healing. Method The data of 234 children with distal tibial epiphysis fractures treated in our hospital from February 2014 to February 2022 were retrospectively analyzed. Imaging data were examined to record epiphyseal grade, fracture type, and the time to appearance of growth arrest lines. Follow-up data were retrieved to record treatment results (i.e., malunion, premature closure, or bone bridge formation). Results There was a significant difference in the time to appearance of growth arrest lines between patients with epiphyseal grade 0–1 and grade 2–3 (P < 0.05) and between patients with normal healing and patients with a bone bridge (P < 0.05). Among patients with normal healing, there were no significant differences in the time to appearance of growth arrest lines between men and women and between patients with and without surgery (P > 0.05). There was a significant difference in the time to appearance of growth arrest lines between patients with different Salter–Harris fracture types (P < 0.05). Conclusion For patients with epiphyseal grade 0–1, the time to appearance of growth arrest lines could be useful for predicting the treatment result of a distal tibial epiphyseal fracture.